Severe cytopenia after CD19 CAR T-cell therapy: a retrospective study from the EBMT transplant complications working party - Penack, Olaf; Peczynski, Christophe; Koenecke, Christian; Polge, Emmanuelle; Kuhnl, Andrea; Fegueux, Nathalie; Daskalakis, Michael; Kröger, Nicolaus; Dreger, Peter; Besley, Caroline; Schanz, Urs; Bloor, Adrian; et al. (Journal for ImmunoTherapy of Cancer, 2023)
We investigated the incidence and outcome of anti-CD19 chimeric antigen receptor (CAR) T-cells-associated Common Terminology Criteria for Adverse Events (CTCAE) ≥grade 3 cytopenia. ...
Gesehen am 05.12.2023